Feasibility Study of Magnesium Slag, Fly Ash, and Metakaolin to Replace Part of Cement as Cementitious Materials - Fulu Wei; Hairong Xiao; Jia Zhang; Zhenqing He; Xuanhao Cao; Bowen Guan (Buildings, 2024)
To achieve the efficient utilization of magnesium slag, this study investigates the use of magnesium slag, fly ash, and metakaolin as partial substitutes for cement in cementitious materials. The reactivity of these materials is assessed based on the compressive strength of mortar. The response surface methodology is employed to explore the influence of material proportions on the strength performance of cement mortar. The mechanisms underlying strength development in the composite system are examined through XRD, SEM, TG-DTG, and BET analyses. Additionally, the effect of magnesium slag on the drying shrinkage properties of cement mortar is studied. The experimental results indicate that magnesium slag exhibits low reactivity and cannot be used alone as an active admixture. The optimal proportion of magnesium slag, fly ash, metakaolin, and cement is 10:10:10:70, achieving over 80% of the strength of pure cement mortar and approximately 1.5 times the strength of cement mortar containing 30% magnesium slag. Furthermore, magnesium slag helps mitigate the volume shrinkage caused by drying in cement mortar. Therefore, this study can facilitate the comprehensive utilization of magnesium slag in the construction sector, reducing its negative impact on the ecological environment.